2017
DOI: 10.33546/bnj.101
|View full text |Cite
|
Sign up to set email alerts
|

Breast Milk as an Alternative for Postpartum Perineal Care

Abstract: Background: Perineal laceration during childbirth is very common among mothers; however some of them may suffer from its complication if not treated properly.Objective: To prove the effectiveness of breast milk as an alternative topical ingredient in the treatment of perineal wound in postpartum mothers.Methods: This was a quasi-experimental study with non-equivalent control group posttest only design. There were 30 respondents selected in this study, with 15 assigned in the intervention and control group. Acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The application of breastmilk topical in the intervention group is more influential than the use of antiseptic soap in the control group. This is because breastmilk contains very useful components to help wound healing and prevention of infection, the antiinflammatory molecules, bioactive substances, and growth factors (Admasari, 2017 Breastmilk in humans remains a unique and high standard for health, in this present study will discuss the advantages of breastmilk in medical treatments, one of them is an alternative medicine in perineal wound healing. Topical breastmilk, especially colostrum is rich in substances of antibody, anti-inflammatory, and leukocytes that play a role in pressing the colonization of pathogenic microorganisms, which can cause wound infections and accelerate the healing time (Subiasturik, 2011).…”
Section: Results and Discussion Tablementioning
confidence: 94%
See 1 more Smart Citation
“…The application of breastmilk topical in the intervention group is more influential than the use of antiseptic soap in the control group. This is because breastmilk contains very useful components to help wound healing and prevention of infection, the antiinflammatory molecules, bioactive substances, and growth factors (Admasari, 2017 Breastmilk in humans remains a unique and high standard for health, in this present study will discuss the advantages of breastmilk in medical treatments, one of them is an alternative medicine in perineal wound healing. Topical breastmilk, especially colostrum is rich in substances of antibody, anti-inflammatory, and leukocytes that play a role in pressing the colonization of pathogenic microorganisms, which can cause wound infections and accelerate the healing time (Subiasturik, 2011).…”
Section: Results and Discussion Tablementioning
confidence: 94%
“…The development and research of perineal wound healing treatment methods say that the healing is not only can be done pharmacological, but also non-pharmacological been able to be developed, one of the alternatives that can be used is breastmilk. Admasari (2017) in the research entitled Breastmilk as an Alternative for Postpartum Perineal Care, showed that the use of breastmilk is more effective than the use of povidone-iodine in perineum wound care as it contains antiinflammatory, bioactive substances and growth factors that can help wound healing and prevention of infection, in addition, the use of breastmilk are harmless, free, available and sterile for perineal injury, this study also had received local permission of ethics research committees so that there are no aggrieved parties.…”
mentioning
confidence: 99%
“…Also, a group of bioactive and anti-inflammatory molecules were known as proresolving mediators (SPMs) that can eliminate the infectious microorganisms, inflammation, and pain in the wound area. Even though the exact mechanism of action remains uncertain, it seems that HM may be a safe and natural substance against foreign and invasive microorganisms due to its rich source of growth factor, anti-inflammatory agents, antibacterial agents, and immunity factors [7].…”
Section: Effects Of Hm On Mothersmentioning
confidence: 99%
“…Approximately 85% of women undergo the episiotomy (perineal area cut) during labor, of which 69% need suture in the area [ 62 ]. Due to the high moisture and low ventilation, the perineal area seems to be a proper environment for the growth of bacteria and invasive microorganisms [ 7 , 63 ]. The perineal inflammations lead to the mother's pain and discomfort and consequently reduced the ability to take care of herself, the baby, and the family.…”
Section: Topical Applications Of Hm (Thm)mentioning
confidence: 99%
See 1 more Smart Citation